Process quality measures and asthma exacerbations in the Medicaid population - Yong, Pierre L.; Werner, Rachel M. (Journal of allergy and clinical immunology, 2009)
Asthma quality assessment often focuses on controller medication use, yet claims-based studies find conflicting associations between this care process and clinical outcomes. We sought to compare the association between 3 controller-based quality measures and asthma exacerbations to gain better understanding of how processes of care are related to clinical outcomes. Identifying a cohort of Medicaid beneficiaries with persistent asthma by using Healthcare Effectiveness Data and Information Set (HEDIS) criteria for asthma in 2001–2002 in California and New York, we assessed 3 asthma quality metrics in 2002: (1) the current HEDIS measure of at least 1 controller medication filling; (2) at least 4 controller medication prescription fillings; and (3) a controller-to-total asthma medication ratio of at least 0.5. We calculated the odds of having an asthma exacerbation in 2003 as a function of performance on each quality metric, adjusting for race, sex, age, and prior outpatient and acute care use for asthma. Of 90,909 subjects with persistent asthma in California (48.1%) and New York (51.9%), those who obtained at least 1 or at least 4 controller medications had increased likelihood of poor outcomes (adjusted odds ratios, 1.80 [95% CI, 1.73–1.87] and 1.44 [95% CI 1.40–1.48], respectively). Beneficiaries meeting the controller-to-total asthma medication ratio measure were 23.0% less likely to have exacerbations (adjusted odds ratio, 0.77 [95% CI, 0.75-0.80]). A higher controller medication ratio indicated a lower likelihood of asthma exacerbations, whereas assessing the number of controller medication–dispensing events was associated with a higher odds of exacerbation.